2001
DOI: 10.1002/pros.1117
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of spread of adenocarcinoma in the prostate as related to cancer volume

Abstract: Patterns and extent of spread of carcinoma in the prostate are stereotyped following a few principles regarding stromal interactions. Using these, sequential maps were presented of evolving prostate cancer contours at consecutive increasing volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 9 publications
7
94
0
2
Order By: Relevance
“…In this study, AFMS cancers still confined to this zone and seen at MRI could be diagnosed by targeted biopsies, whereas they were not observed at this stage in previous series of RP before the DCE-MRI era (Fig. 2) [10]. Improvement in imaging necessitates better knowledge of depiction of these intraprostatic cancers from histopathological studies.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…In this study, AFMS cancers still confined to this zone and seen at MRI could be diagnosed by targeted biopsies, whereas they were not observed at this stage in previous series of RP before the DCE-MRI era (Fig. 2) [10]. Improvement in imaging necessitates better knowledge of depiction of these intraprostatic cancers from histopathological studies.…”
Section: Introductionmentioning
confidence: 48%
“…Prostatectomy specimens were inked, fixed and sectioned according to the Stanford protocol [10]. A histological map of each prostate was performed from whole-mount histological slides.…”
Section: Histological Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition zone tumors tend to stay in the zone where they first developed until they have reached a volume between 2 and 4 cm 3 . 36 Transition zone cancers are usually considered to have a better outcome at same volume and grade than their peripheral zone counterparts. [37][38][39] Demichelis et al 5 characterized the TMPRSS2-ERG fusion status in a population-based cohort of men with early prostate cancer diagnosed by transurethral resection of the prostate or transvesical adenoma enucleation for symptomatic benign prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most common interaction between nerves and prostate epithelium during tumorigenesis is PNI. The biological and clinical significance of PNI in prostate cancer has been the subject of intense debate (15)(16)(17)(18). Numerous other authors have reported varying degrees of clinical prognostic significance for PNI (15, 17, 19 -23).…”
Section: Discussionmentioning
confidence: 99%